2013
DOI: 10.1371/journal.pgen.1003319
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Chromatid Separation and Spindle Elongation by Antagonistic Activities of Mitotic and S-Phase CDKs

Abstract: Because cohesion prevents sister-chromatid separation and spindle elongation, cohesion dissolution may trigger these two events simultaneously. However, the relatively normal spindle elongation kinetics in yeast cohesin mutants indicates an additional mechanism for the temporal control of spindle elongation. Here we show evidence indicating that S-phase CDK (cyclin dependent kinase) negatively regulates spindle elongation. In contrast, mitotic CDK promotes spindle elongation by activating Cdc14 phosphatase, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…We found that a group of Cdk1 targets that are dephosphorylated in anaphase, Fin1, Spc110, and Cnn1 (Woodbury & Morgan, 2007; Bock et al , 2012; Liang et al , 2013) contain Clb5‐specific NLxxxL motifs (Fig 7D). We analyzed the cyclin specificity of phosphorylation of these substrates and confirmed that, as predicted, Fin1, Spc110, and Cnn1 are most efficiently phosphorylated by Clb5‐Cdk1, when compared with Clb3‐ and Clb2‐Cdk1 (Fig 7E).…”
Section: Resultsmentioning
confidence: 86%
“…We found that a group of Cdk1 targets that are dephosphorylated in anaphase, Fin1, Spc110, and Cnn1 (Woodbury & Morgan, 2007; Bock et al , 2012; Liang et al , 2013) contain Clb5‐specific NLxxxL motifs (Fig 7D). We analyzed the cyclin specificity of phosphorylation of these substrates and confirmed that, as predicted, Fin1, Spc110, and Cnn1 are most efficiently phosphorylated by Clb5‐Cdk1, when compared with Clb3‐ and Clb2‐Cdk1 (Fig 7E).…”
Section: Resultsmentioning
confidence: 86%
“…Previous work showed that Net1 phosphorylation by Clb2/Cdk1 triggers Cdc14 release, and mutation of the six phosphorylation sites ( net1-6Cdk ) blocks FEAR activation and the premature Cdc14 release in cdc55 Δ mutants (Azzam et al, 2004; Liang et al, 2013). To further assess if the sensitivity of cdc55 Δ swe1 Δ cells to syntelic attachment is due to hyperactive FEAR, we compared the growth of cdc55 Δ swe1 Δ and cdc55 Δ swe1 Δ net1-6Cdk cells overexpressing CIK1-CC.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of PP2A regulatory gene CDC55 leads to premature Cdc14 release (Liang et al, 2009; Wang and Ng, 2006). FEAR-dependent Cdc14 release specifically reverses the phosphorylation imposed by S-phase CDK to facilitate anaphase progression (Jin et al, 2008; Liang et al, 2013). Fin1 is a verified S-phase CDK substrate (Loog and Morgan, 2005), and its phosphorylation promotes its interaction with 14-3-3 proteins, Bmh1 and Bmh2, which prevents the kinetochore association of Fin1 (Akiyoshi et al, 2009; Mayordomo and Sanz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…At lower temperature, however, pds1Δ cells are viable but chromosome loss is frequent and many cells cannot form colonies (Yamamoto et al. , 1996a; Liang et al. , 2013).…”
Section: Resultsmentioning
confidence: 99%